Costs and benefits of regulation : implications for developing countries - Guasch, J. Luis (1999)
Examines the literature on the benefits and costs of regulation and finds that it demonstrates that this issue can be explored systematically using standad economic analysis. Discusses that regulation can have a significant adverse impact on economic growth and in addition process regulation can impose a significant cost on the economy. Notes that social regulation may have significant net benefits for the average consumer if designed judiciously. Suggests that there are several policies developing countries might consider adapting to improve their general approach to regulation.